AUTOMATIC CONTROL SYSTEMS - Tashkoziyeva, Zulfiya Eraliyevna (Educational Research in Universal Sciences, 2023)
Introducing students to the types of automatic control systems. A set of measures that implements the process in a certain sequence and without human intervention includes the automatic control of the technological process and the control of the zagotovka processing on metal cutting machines, the frequency of rotation of the spindle, the speed of the pivoting and daily movements of the support or table, or the position of the revolver head. These controlled quantities are represented by the control parameters of the process.